2013
DOI: 10.1108/17538371311319025
|View full text |Cite
|
Sign up to set email alerts
|

Temporary project network and innovation: research on the Italian regional wine industry

Abstract: PurposeThis study aims at exploring the characteristics of the Temporary Project Networks (TPNs) in small and medium-sized wine producing enterprises, both from a theoretical and an empirical perspective. It aims to discuss different types of temporary inter-firm collaboration clusters both in terms of structural/organizational features and in terms of innovation tasks development. It also aims to develop an empirically derived taxonomy of TPNs within the Sannio wine industry. Design/methodology/approachThe pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…We chose this particular firm for the case study because it offered a consistent rich setting for studying knowledge. On the basis of the information from the earlier survey (Pezzillo Iacono et al ., ), the company proved, through its significant product and process innovations in terms of both technology and “semantics” to have a strong drive toward internationalization and a conscious approach to acquiring both implicit and explicit knowledge. In addition, the organizational model—a winemaking cooperative—is a common one both in Italy and in the local area.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We chose this particular firm for the case study because it offered a consistent rich setting for studying knowledge. On the basis of the information from the earlier survey (Pezzillo Iacono et al ., ), the company proved, through its significant product and process innovations in terms of both technology and “semantics” to have a strong drive toward internationalization and a conscious approach to acquiring both implicit and explicit knowledge. In addition, the organizational model—a winemaking cooperative—is a common one both in Italy and in the local area.…”
Section: Methodsmentioning
confidence: 99%
“…The wine industry has been involved in a process of technological innovation within which knowledge creation and knowledge sharing have taken on a much more significant role (Pezzillo Iacono et al ., ). Technical change has been strong, and the key competitive asset of wine producers is now the capacity to assimilate, develop, and manage new techniques of production.…”
Section: Research Contextmentioning
confidence: 97%
See 2 more Smart Citations
“…Second, as it is common in literature, we selected a case study in which the phenomena of interest about the use of knowledge integration mechanisms in a University/Industry collaboration setting are transparently observable. Finally, earlier work (Pezzillo Iacono et al , 2013) focused on the leading player in the research project, the Farming Cooperative La Guardiense , suggested that the company had significant product and process innovation in terms of both technology and “semantics”, providing a strong drive towards a conscious approach to managing knowledge.…”
Section: Methodsmentioning
confidence: 99%